Implementation and scaling-up of an effective mHealth intervention to increase adherence to triage of HPV-positive women (ATICA study): perceptions of health decision-makers and health-care providers - Sánchez Antelo, Victoria (2023)
Fil: Straw, Cecilia. University of Buenos Aires. Faculty of Social Sciences; Argentina.